Managing change and the related performance dimensions of multiple-discipline science and medical services departments in high performance sports organizations: a systematic review - Anderson, F. O. J.; Mugford, A.; Bredin, S.; Scott, A.; Taunton, J.; Warburton, D. (Research & Investigations in Sports Medicine, 2020)
Rationale: To synthesize evidence related to effective practices, in relation to change management and performance management dimensions, in multiple-discipline science and medical services departments. Methodology: Systematic review, employing a search and screening strategy, in accordance with the PRISMA protocol. Data sources:Web of Science, Sport Discus, Cinahl, Medline, PubMed Eligibility criteria: Primary empirical evidence, published in English language peer reviewed journals, related to change management or performance management dimensions, as demonstrated in the service provision by multiple-discipline science and medical services departments in high performance sports organizations. Findings: Twenty studies satisfied the inclusion criteria. Thematic synthesis identified factors related to foundational perspectives of change management and dimensions of performance management, across the following themes: micro perspectives of change management, meso perspectives of change management, macro perspectives of change management, strategic performance management, operational performance management, individual performance management and leadership of the multiple-discipline science and medical services team. Practical implications: Guidance is provided in relation to the training and practical application of skills required by practitioners operating in such leadership roles. Research contribution: Implications for high performance sports organizations are considered across these themes, in relation to the identification, recruitment and continuing development of suitable multiple-discipline science and medical services department directors.